Kontribusi Fasilitas Belajar, Minat Masuk Sekolah Kejuruan Dan Lingkungan Belajar Terhadap Kemandirian Belajar Siswa Kelas X Smkn 1 Jenar Sragen Tahun 2015/2016 - Partono, Partono; , Prof.Dr. Budi Murtiyasa,M.Kom; , Idris Harta, M.A., Ph.D (2016)
ABSTRACT PARTONO NIM Q100140060 title "Contributions of Learning Facilities, Interests Sign vocational and Learning Environment Against Independence of Student Learning class X SMK N 1 jenar, Sragen academic year 2015 / 2016.Tesis Muhammadiyah University of Surakarta. Purpose of this study to examine the contribution of learning facilities, interest in vocational and environments of class X student of SMK N 1 jenar, Sragen 2015/2016 school year partially or simultaneously. Type diskritif quantitative research, the study was conducted on 129 samples with sampling techniques responden Pengambilan sistematis.Teknik data collection with questionnaires and data retrievwith kuisioner.Teknik regression data analysis, test the accuracy of the model, test the accuracy of parameter estimators, relative contributions, and test classical assumptions.Results of this study stated that 1) Contributions of learning facilities (X1) to independent learning (Y) class X SMK N 1 jenar Sragen. The learning facilities contribute effectively amounted to 17.40%, and a significance level of 5% reinforced grades sig 0.000 <0,05.2) Contributions interest in SMK (X2) towards independent learning (Y) class X SMK N 1 jenar Sragen.Minat enter vocational contribute effectively amounted to 26.94%, with a significance level of 5% reinforced grades sig 0.000 <0.05. 3) Contribution learning environment (X3) against independent learning (Y) class X SMK N 1 jenar Sragen, Environment provides effective contribution of 8.59%, and a significance level of 5% reinforced grades sig 0.000 <0.05. 4) Facility, interest in vocational and environment simultaneously significant and positive impact on the independence of the variables studied, with Koesfisien Determination 52.9%, with a significance level of 5% reinforced grades sig 0.000 <0.05. Keywords: facilities, environment, interests, independence